Politica monetaria, produzione e problemi di incoerenza temporale - Antonello Eugenio Scorcu (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1991)
– This work extends the analysis of time inconsistency in monetary policy to the case of serial correlation in the level of production. In the one-shot discretionary equilibrium Inflation is higher than in the Barro-Gordon case. Over an infinite horizon, output persistence makes the conditions for a reputational equilibrium more likely to be met.
Keywords: 330